Stigma Among Older Adults With Age-Related Vision Impairments. (September 2022) - Kumar, Priyanka; Campanile, Jessica; Swenor, Bonnielin K.; Varadaraj, Varshini
Introduction: Limited research has examined the experience and psychosocial effect of vision impairment in older adults. We examine the relationship between vision impairment and stigma using guided interviews among older adults with age-related eye disease.Methods: Thirty-six participants with vision impairment were recruited from glaucoma ( n = 18) (better eye visual fields mean deviations: >5 and <15 decibels) or retina ( n = 18) (better eye visual acuity: <20/40 and >20/400) clinics of the Johns Hopkins Wilmer Eye Institute between 2015 and 2020. Participants completed interviews to examine stigma surrounding age-related vision impairment. Interviews were transcribed and analyzed using directed content analysis.Results: Content analyses of interview transcripts revealed underlying stigma within our cohort. Starting with categories of (1) interpersonal relationships and (2) evolving self-perception, specific domains of stigma were realized in this study. Although both enacted (external) stigma and perceived stigma were acknowledged by a subset of participants, few endorsed internalized stigma. In the face of stigma, participants demonstrated notable resiliency in adapting to and living with age-related vision impairment, captured in an additional category of (3) behavioral adaptations.Discussion: In-depth interviews revealed that older adults with vision impairment confront specific domains of stigma, including enacted and perceived stigma. Features protective against internalized stigma included older age, community support, and assistive technologies.Implications for Practitioners: A recognition of the subtypes of stigma that older adults with age-related vision impairment face is necessary to tailor support and target interventions.